Peran Koperasi Syariah dalam Upaya Meningkatkan Perekonomian Anggotanya Menurut Perspektif Islam - Sholihah, Isfi; Juaini, Muhamad; Jailani, Huzain; Liana, Emi (Alpatih Harapan Semesta, 2025)
Sharia cooperatives are legal entities and family-based businesses that prioritize a sense of brotherhood among all members based on Islamic sharia, namely the Qur'an and Sunnah. The purpose of the sharia cooperative itself is to advance the economy of its members and society in general. The main issue that arises in this research is: What is the role of the Surya Ganda Lestari Sharia Cooperative from the perspective of Islamic economics? What are the challenges faced by Koperasi Syariah Surya Ganda Lestari in managing its business? And also, what solutions have been implemented by the Syariah Cooperative Surya Ganda Lestari to address the issues that have arisen? This research aims to provide an understanding of the role of sharia cooperatives in improving the economy of their members. The research conducted is qualitative research using a descriptive design. The subjects of this research include all employees of Koperasi Syariah Surya Ganda Lestari, informants, including cooperative managers, cooperative supervisors, and employees or members of Koperasi Syariah Surya Ganda Lestari. This research includes field studies, data collected through direct observation, data analysis, and drawing conclusions. The data collection techniques used are interviews, observations, and documentation. The research results obtained show that 1) Koperasi Syariah Surya Ganda Lestari provides a significant contribution to the economic welfare of its pre-members 2) The existing obstacles are problematic loans, and there is still a fine system in the cooperative, 3) The solution is, in addressing problematic loans: by rescheduling, setting requirements, and organizing. In handling fines: For customers who are unable to pay their bills, the cooperative should forgive and guide those customers. Sharia cooperatives must maintain their existence, innovation, and support from the community.